2017
DOI: 10.1038/mi.2016.97
|View full text |Cite
|
Sign up to set email alerts
|

The rectal mucosa and condomless receptive anal intercourse in HIV-negative MSM: implications for HIV transmission and prevention

Abstract: Most HIV transmissions among men who have sex with men (MSM), the group that accounted for 67% of new US infections in 2014, occur via exposure to the rectal mucosa. However, it is unclear how the act of condomless receptive anal intercourse (CRAI) may alter the mucosal immune environment in HIV negative MSM. Here, we performed a comprehensive characterization of the rectal mucosal immune environment for the phenotype and production of pro-inflammatory cytokines by CD4 and CD8 T cells, global transcriptomic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
148
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(167 citation statements)
references
References 53 publications
15
148
4
Order By: Relevance
“…The study was not powered to address alterations in numbers of colonic cytokine-producing ILCs in the setting of HIV-1 infection. The two study groups were not matched for sexual practice, which has recently been reported to impact the intestinal microbiome independent of HIV-1 infection 49,50 and may drive mucosal immune cell activation and inflammation 50 and therefore be a contributing factor to our current observations. Enumeration of the specific ILC subsets was based on criteria used to identify NK22 cells 16 .…”
Section: Discussionmentioning
confidence: 96%
“…The study was not powered to address alterations in numbers of colonic cytokine-producing ILCs in the setting of HIV-1 infection. The two study groups were not matched for sexual practice, which has recently been reported to impact the intestinal microbiome independent of HIV-1 infection 49,50 and may drive mucosal immune cell activation and inflammation 50 and therefore be a contributing factor to our current observations. Enumeration of the specific ILC subsets was based on criteria used to identify NK22 cells 16 .…”
Section: Discussionmentioning
confidence: 96%
“…First, we lack data on the sexual preference of our control group that is needed to assess the impact of HIV on the gut microbiome while controlling for sexual behavior. Interestingly, Prevotellaceae enrichment was found in most but not all MSM who engaged in CRAI19 suggesting that the factors driving Prevotella -rich microbiotas in MSM population are still unclear. In the light of recent publications1619, we are actively recruiting HIV-negative MSM to characterize their fecal microbiome and continue our research goal, which is to truly understand changes in the gut microbiome that are driven by HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Prevotellaceae enrichment was found in most but not all MSM who engaged in CRAI19 suggesting that the factors driving Prevotella -rich microbiotas in MSM population are still unclear. In the light of recent publications1619, we are actively recruiting HIV-negative MSM to characterize their fecal microbiome and continue our research goal, which is to truly understand changes in the gut microbiome that are driven by HIV. Also, the number of HIV SN individuals is relatively small and should be increased to fully characterize the baseline microbiome of HIV-uninfected individuals in Mexico.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the T cells localized in the rectum are activated and express increased CCR5, a coreceptor used by HIV-1 for cell attachment. A recent study showed that MSM who engage in condomless RAI had a change in the activation status of immune cells [29]. Additionally, a marked change in the anorectal microbiota to a species ( Prevotella ) that could increase HIV transmission by increasing inflammation was also observed.…”
Section: Design Considerations For On-demand Productsmentioning
confidence: 99%